Critical undrained shear strength of sand-silt mixtures under monotonic loading (2014)
This study uses experimental triaxial tests with monotonic loading to develop empirical relationships to estimate undrained critical shear strength. The effect of the fines content on undrained shear strength is analyzed for different density states. The parametric analysis indicates that, based on the soil void ratio and fine content properties, the undrained critical shear strength first increases and then decreases as the proportion of fines increases, which demonstrates the influence of fine content on a soil’s vulnerability to liquefaction. A series of monotonic undrained triaxial tests were performed on reconstituted saturated sand-silt mixtures. Beyond 30% fines content, a fraction of the silt participates in the soil’s skeleton chain force. In this context, the concept of the equivalent intergranular void ratio may be an appropriate parameter to express the critical shear strength of the studied soil. This parameter is able to control the undrained shear strength of non-plastic silt and sand mixtures with different densities. ResumenEste estudio utiliza evaluaciones experimentales triaxiales con cargas repetitivas para desarrollar relaciones empíricas y estimar la tensión crítica de corte bajo condiciones no drenadas. El efecto de contenido de finos en la tensión de corte sin drenar se analizó en diferentes estados de densidad. El análisis paramétrico indica que, basado en la porosidad del suelo y las propiedades del material de finos, la tensión de corte sin drenar primero se incrementa y luego decrece mientras la proporción de finos aumenta, lo que demuestra la influencia de contenido de finos en la vulnerabilidad del suelo a la licuación. Una serie de las evaluaciones se realizó en  mezclas rehidratadas y saturadas de arena y cieno. Más allá del 30 % de los contenidos finos, una fracción del cieno hace parte principal de la cadena de fuerza del suelo. En este contexto, el concepto de porosidad equivalente intergranular puede ser un parámetro apropiado para expresar la tensión crítica de corte del suelo estudiado. Este parámetro nos permite controlar la tensión de corte sin drenar de cieno no plástico y mezclas de arena de densidades diferentes.